(untitled) (Nigerian Journal of Physiological Sciences, 2023)
This study examines the effect of gestational administration of aqueous leaf extract of Jatropha tanjorensis (JT) on postpartum-like behavioural outcomes to delineate its possibility as a prophylactic, therapeutic agent in the treatment of postpartum symptoms. Inseminated female rats (120-150g) were grouped into two-control and JT group (n=10). Control received 20 ml/kg of distilled water and JT group received 500 mg/kg of JT orally once daily for 21 days in gestation. Non-pregnant rats were excluded from the study. Parameters assessed at postpartum include antidepressant-like (force swim test, FST; tail suspension-test, TST), locomotor (open field test, OFT), anxiolytic-like (elevated plus maze, EPM; light-dark box, LDB), learning and memory (T-maze; novel object recognition task, NORT), social (nest score) and analgesic-like (hot plate test, HPT; tail flick test, TFT) behaviours. JT increased (P<0.05) mobility and latency to immobility durations in FST and TST; open arm entry (P<0.001) and duration (P<0.01) in EPM and light box duration (P<0.05) in LDB; locomotion and exploration, but reduced anxiety-like levels in EPM, LDB and OFT. It increased nest score (P<0.05); mean retraction time (P<0.01) of TFT. JT showed positive score for short and long term memory in NORT and improved percentage alternation in T-maze though not significant compared to control. In conclusion, the aqueous extract has a therapeutic effect that reduces postpartum-like depression and anxiety, and improves locomotor activity. JT can be a preventive and adjuvant therapeutic option for pregnant women